Working with female offenders in restorative justice frameworks: effective and ethical practice - Masson, Isla (Probation journal, 2017)
Despite a recent increase in restorative justice practice in the criminal justice system, to date there has been no in-depth consideration of the impact of gender in these settings. This paper presents findings from a unique qualitative study on female offenders’ experiences of restorative conferencing in England and Wales, drawing on interviews with practitioners who have worked with female cases, as well as with women who have gone through a restorative justice conference in a perpetrator capacity. Gender-specific factors, suggested to be especially valuable for practitioners to consider when delivering effective and ethical restorative conferences with female offenders, are outlined.